EVALUASI KETERAMPILAN BERMAIN SEPAK BOLA PADA SSB BINTANG GARUDA FC ACEH BESAR - Kurniawan, Erizal; Khairi, Miftahul; Musran, Musran; Syahrianursafi, Syahrianursafi (Jurnal Dedikasi Pendidikan, 2022)
Mastering basic skills is the main capital for playing soccer, without ignoring physical and mental needs. Having basic skills will make it easier to play soccer either to score goals or teamwork. The purpose of this study was to determine the results of the evaluation of soccer playing skills at SSB Bintang Garuda FC Aceh Besar. This research approach is qualitative with the type of evaluation. The population and sample of this study were 30 SSB Bintang Garuda FC Aceh Besar players with purposive sampling technique. This research data collection technique uses a basic soccer skills test instrument aged 10-12 years consisting of: dribbling test, short passed, throw in, running with the ball, heading the ball, and shooting at the ball. The results of the research obtained are the soccer playing skills of Bintang Garuda FC Aceh Besar as follows: 1) good category with a frequency of 18 players (60.00%), 2) medium category with a frequency of 11 players (36.67%), and 3) less category with a frequency of 1 player (3.33%).  The conclusion of the study is that the soccer playing skills of Bintang Garuda FC Aceh Besar are in the good category